1995
DOI: 10.1016/s0022-5347(01)66780-6
|View full text |Cite
|
Sign up to set email alerts
|

Benign Prostatic Hyperplasia Specific Health Status Measures in Clinical Research: How Much Change in the American Urological Association Symptom Index and the Benign Prostatic Hyperplasia Impact Index is Perceptible to Patients?

Abstract: These data provide guidance for investigators using the AUA symptom index and BPH impact index as outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
306
10
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 444 publications
(332 citation statements)
references
References 6 publications
8
306
10
8
Order By: Relevance
“…At 3 months the improvement had stabilized in the TUMT and control groups, whereas the results in the ILC group improved further at 3-6 months. At 6 months the difference in IPSS between the experimental and the control group was lower than the pre-set minimal relevant difference, and thus less than that which Barry et al [21] found to be perceptible to mildly symptomatic patients. However, because fewer patients were included in the study and there was a larger than anticipated variability in IPSS, the confidence limits for the differences were wide and the data support the view that there could be differences larger than the pre-set minimal relevant difference in favour of TURP/TUIP.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…At 3 months the improvement had stabilized in the TUMT and control groups, whereas the results in the ILC group improved further at 3-6 months. At 6 months the difference in IPSS between the experimental and the control group was lower than the pre-set minimal relevant difference, and thus less than that which Barry et al [21] found to be perceptible to mildly symptomatic patients. However, because fewer patients were included in the study and there was a larger than anticipated variability in IPSS, the confidence limits for the differences were wide and the data support the view that there could be differences larger than the pre-set minimal relevant difference in favour of TURP/TUIP.…”
Section: Discussioncontrasting
confidence: 52%
“…Thus, the IPSS was chosen as the primary outcome measure, as the perceptibility of this instrument as been assessed [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This index is typically used to identify changes in disease progression over time, where most patients identify a decrease in three points as a clear improvement. 50 It has been shown by Moon et al 51 that socioeconomic factors do not seem to have an effect on the responses given to the questionnaire and by Barry et al 52 that the responses generated from the questionnaire are the same regardless of whether it is self-administered, read to the patient, mailed in or administered in an alternative way. This does not exclude the possible differences that may arise in terms of how the questionnaire or symptoms are perceived by patients.…”
Section: Symptom Scorementioning
confidence: 99%
“…[60][61][62][63][64][65][66][67][68] Another weakness of using the maximum flow rate to diagnose BPH is that is tends to have diurnal and day to day variability. 50,69 Most BPH trials tend to use flow rates less than 10-15 ml s À1 as entry criteria. Lower baseline flow rates do correlate with higher rates of BPH progression, but ultimately, it would require urodynamic studies to determine if this is due to bladder function or symptoms secondary to obstruction.…”
Section: Maximum Flow Ratesmentioning
confidence: 99%